2015
DOI: 10.1007/s15010-014-0718-x
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic consumption after implementation of a procalcitonin-guided antimicrobial stewardship programme in surgical patients admitted to an intensive care unit: a retrospective before-and-after analysis

Abstract: Implementation of an ASP in conjunction with a PCT protocol in 2011 was associated with a marked decrease in total AD and led to a significant change in the spectrum of antibiotics. Clinical outcomes appeared to remain unchanged over the study period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
3
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 28 publications
1
29
3
1
Order By: Relevance
“…However, the current use of PCT for stewardship of antibiotic therapy duration in patients after surgery, or with community-acquired pneumonia, may provide a compelling argument that PCT levels respond quickly to changes in inflammatory and infectious conditions. [57, 58]. Also, an in vivo half-life of 22–25 hours provides a rationale for a shorter prohibited period.…”
Section: Discussionmentioning
confidence: 99%
“…However, the current use of PCT for stewardship of antibiotic therapy duration in patients after surgery, or with community-acquired pneumonia, may provide a compelling argument that PCT levels respond quickly to changes in inflammatory and infectious conditions. [57, 58]. Also, an in vivo half-life of 22–25 hours provides a rationale for a shorter prohibited period.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical outcomes reported often utilise routinely collected data, which may 241 explain the differences between the community and hospital setting. In particular, in the hospital setting, 242 commonly used clinical outcomes are mortality and length of hospital stay [18,19]. As indicated by the 243 observed time trends, these outcomes are being used with increasing frequency, probably because 244 extraction of relevant data from electronic health records is becoming more feasible.…”
mentioning
confidence: 99%
“…Core strategies of hospital antimicrobial stewardship programmes (ASP) are [40] Retrospective data from a surgical ICU showed a marked reduction (−21.2 %) of antibiotic use density after implementation of a local antibiotic stewardship programm in conjunction with a PCT protocol [9].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to adhere to established protocols with daily PCT monitoring to assess the dynamics of this biomarker [8]. Clinical studies in various diseases have shown that PCT-guided algorithms result in positive long-term effects with respect to frequency and length of antibiotic treatment in intensive care patients [9,10]. Clinicians have to keep in mind that trauma, surgical interventions, or multiorgan failure may lead to increased PCT levels in the absence of underlying infections [11,12].…”
Section: Introductionmentioning
confidence: 99%